Lucky you : a novel - Hiaasen, Carl. (New York : Alfred A. Knopf, 1997)
JoLayne Lucks is one of the winners of the Florida state lottery of $28 million. The other winners, Bodean Gazzer and his sidekick, steal her ticket to start their own underground militia. When Lucks vows to take it back and get revenge, the humor begins.
Keywords: Lottery winners -- Florida -- Fiction; White supremancy movements -- Florida -- Fiction; Florida -- Fiction; Humorous fiction